PENGARUH MOTIVASI, KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI PERSEROAN TERBATAS BANK NEGARA INDONESIA (PERSERO) TERBUKA KCU TEGAL - Deasy Deasy; Ratih Ratih (BBM (Buletin Bisnis & Manajemen), 2018)
The purpose of this study is to determine the effect of motivastion, job satisfaction, work environment on employee performance PT Bank Negara Indonesia (Persero) Tbk KCU Tegal.Data were obtained through questionnaires and interviews. The sample used in the study of 108 respondents. Results are expected to provide useful information to both leaders and employees. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis using multiple regression analysis to determine the effect of independent variables on the dependent variable, but before the test is done first tested the validity and reliability testing as well as testing requirements.The analysis shows that there is there is the influence of motivation on the performance, the influence of experience on the performance, and influence work environment positively and significantly to the performance of Employee PT Bank Negara Indonesia (Persero) Tbk KCU Tegal.